A Double-Blind, Randomized Clinical Trial of Niacinamide 4% versus Hydroquinone 4% in the Treatment of Melasma - Josefina Navarrete-Solís; Juan Pablo Castanedo-Cázares; Bertha Torres-µlvarez; Cuauhtemoc Oros-Ovalle; Cornelia Fuentes-Ahumada; Francisco Javier González; Juan David Martínez-Ramírez; Benjamin Moncada (Dermatology Research and Practice)
Background. Multiple modalities have been used in the treatment of melasma with variable success. Niacinamide has anti-inflammatory properties and is able to decrease the transfer of melanosomes. Objective. To evaluate the therapeutic effect of topical niacinamide versus hydroquinone (HQ) in melasma patients. Patients and Methods. Twenty-seven melasma patients were randomized to receive for eight weeks 4% niacinamide cream on one side of the face, and 4% HQ cream on the other. Sunscreen was applied along the observation period. They were assessed by noninvasive techniques for the evaluation of skin color, as well as subjective scales and histological sections initially and after the treatment with niacinamide. Results. All patients showed pigment improvement with both treatments. Colorimetric measures did not show statistical differences between both sides. However, good to excellent improvement was observed with niacinamide in 44% of patients, compared to 55% with HQ. Niacinamide reduced importantly the mast cell infiltrate and showed improvement of solar elastosis in melasma skin. Side effects were present in 18% with niacinamide versus 29% with HQ. Conclusion. Niacinamide induces a decrease in pigmentation, inflammatory infiltrate, and solar elastosis. Niacinamide is a safe and effective therapeutic agent for this condition.